Lithofacies Types, Assemblage Characteristics, and Sedimentary Evolution Model of Lacustrine Shale in Dongyuemiao Formation of Fuxing Area - Shu, Yi; Bao, Hanyong; Zheng, Youheng; Chen, Miankun; Lu, Yongchao; Liu, Haotian; Peng, Wei; Zhou, Lin; Ma, Yiquan; Wen, Yaru; Wang, Qiming; Zhang, Zhiyao (Frontiers in Earth Science, 2021)
Abstract: The identification and classification of lithofacies types is one of the important basic work for shale oil and gas exploration and development evaluation. At present, numerous studies have focused on the classification of lithofacies in marine shale, but the research on lacustrine shale lithofacies is still in its infancy. Therefore, this study takes the shale of Jurassic Dongyuemiao formation in Fuxing area as the research object, combined with the technical means of core observation, thin section identification, XRD, wavelet transform, and through the fine identification and characterization of the shell fossils layer in this formation. On the basis of establishing the high-resolution sequence stratigraphic framework, the lithofacies types and lithofacies assemblages are divided, the lithofacies characteristics and sedimentary evolution models in different sequence units are analyzed, besides, the significance of lithofacies assemblages for shale oil and gas exploration is discussed. The study shows that the shale of the target interval can be divided into 8 parasequence sets, and a total of 9 types of lithofacies and 6 types of lithofacies assemblages are identified: massive bioclasts limestone shoal facies (LF1), thick layered shell fossils limestone facies (LF2), layered Mud-bearing shell fossils limestone facies (LF3), laminated shell fossils argillaceous shale facies (LF4), laminated shell fossils-bearing argillaceous shale facies (LF5), argillaceous shale facies (LF6), massive storm event bioclasts facies (LF7), massive argillaceous limestone facies (LF8) and massive mudstone facies (LF9). The sedimentary evolution models of different lithofacies are established respectively: Unit 1 (LF1-LF6) of the Dong-1 member is the early stage of the lake transgressive system tract, Units 2-4 (LF4-LF7) corresponds to the middle late stage of the lake transgressive system tract, which is an anoxic sedimentary environment, and the Dong-2 member (LF7-LF8) and Dong-3 member (LF5+LF9) correspond to the lake reg